Desenvolvimento de materiais para ortodontia: resina 3D incorporada com cardanol para alinhadores e bráquete metálico modificado - Salgado, Alexandre Daher Yunes (2025)
The pursuit of workflow optimization in the production of orthodontic aligners has driven the development of methods and materials aimed at reducing steps, costs, and environmental impacts while enhancing device precision and customization. Direct 3D printing of aligners represents a promising approach in this context. To enable this technique, the biomaterial cardanol emerges as a potential additive for 3D resin formulation due to its flexibility and resilience. Despite the increasing popularity of aligners, fixed appliances remain the gold standard in Orthodontics. Proper bracket bonding to teeth is essential for treatment success; however, the opacity of metallic materials limits resin polymerization, particularly at the central region of the bracket base. A modified bracket design was proposed to improve light penetration and optimize polymerization. This dissertation is divided into two chapters. Chapter 1 addresses the patent for a 3D resin developed for the printing of orthodontic aligners, while Chapter 2 describes research on a modified metallic bracket. The objective of Chapter 1 was to develop and file a patent for an invention related to the synthesis and dental application of a cardanol-incorporated 3D resin for orthodontic aligner printing. The patent was drafted and filed with the INPI. Chapter 2 aimed to evaluate the performance of a modified metallic bracket regarding shear bond strength (SBS), adhesive remnant index (ARI), and degree of conversion (DC) of the orthodontic resin. Twenty-eight bovine teeth were halved for testing. After acid etching, Orthocem® resin was used for bracket bonding. Five groups were tested: control with a standard bracket (CB), control with a standard bracket subjected to thermocycling (CB-T), and three experimental groups with a modified bracket featuring a central 0.8 mm hole: spot bracket resin (SBR), spot bracket resin thermocycled (SBR-T), and spot bracket enamel (SBE). SBS tests were conducted using a universal testing machine 24 hours after bonding for the CB, SBR, and SBE groups, and after thermocycling for the CB-T and SBR-T groups. ARI was assessed under a stereomicroscope, and resin DC was evaluated using micro-Raman spectroscopy. Statistical analysis included ANOVA with Tukey’s post hoc test for SBS, Kruskal-Wallis for ARI, and Student’s t-test for DC. Results showed higher mean SBS in the SBE experimental group (10.33 ± 2.55 MPa) compared to the control group (CB) (8.77 ± 4.58 MPa) (p=0.737). Thermocycling did not result in significant differences (p=1.00) between groups. Similarly, ARI did not vary significantly (p=0.113). However, the experimental group exhibited higher resin DC (49.3%) compared to the control (25.9%) (p=0.02). The modified bracket demonstrated improved resin DC, although this did not translate into a significant increase in bonding strength.